Exploration relation between interlaminar shear properties of thin-ply laminates under short-beam bending and meso-structures. (July 2018) - Huang, Chunfang; He, Mingchang; He, Yonglyu; Xiao, Jiayu; Zhang, Jiangwei; Ju, Su; Jiang, Dazhi
Carbon fiber reinforced polymer matrix composite laminates with standard thickness plies (0.125 mm) usually have weak interlaminar shear strength, meanwhile, for thin-thickness laminate structures such as aircraft wing skin, it is difficult to design a balanced laminate with the standard plies. It is a possible way to improve the interlaminar shear performance of carbon fiber reinforced polymer composite laminates and enlarge the design space of the thin-thickness structures by using thin-plies technology. In this paper, the interlaminar shear strength of carbon fiber/epoxy laminates with thin prepreg thickness subjected to short-beam bending is investigated. Unidirectional, cross-ply and quasi-isotropic laminate specimens were prepared by using prepregs with different ply thicknesses. Results show that, with decreasing of the ply thickness, higher interlaminar shear strength and smaller coefficient of variation of the data are obtained. Compared to laminates made by standard thickness prepreg, the laminates with thin-thickness prepreg exhibit more homogeneous microstructures and more regularly interlaminar shear stress distribution. This indicates that inherent anisotropy of the laminate composites is weakened in the thin-ply laminates and show pseudo-isotropic behavior. Especially in the case of ply thickness less than 0.020 mm, the interlaminar shear stress distributions of the cross-ply and quasi-isotropic laminate are almost the same with that of isotropic materials according to the classic laminate theory. On the other hand, as expected, the design space of the thin-thickness laminate structures will be increased since more ply number are allowed and superior interlaminar properties can be obtained due to the pseudo-isotropic behavior of the thin plies.